Les Goitres Plongeants : Aspects Épidémiologiques, Cliniques, Radiologiques Et Thérapeutiques - Illé S; James Didié L; Bako I; Sani Rachid (European Scientific Journal, ESJ, 2016)
Purpose: To describe the epidemiological and diagnostic aspects and surgical treatment procedures of plunging goiter in the Oto-Rhino- Laryngology and Neck Surgery Office of the National Hospital of Niamey in Niger. Materials and Methods: We analyzed the clinical and paraclinical symptoms as well as the technique and postoperative evolution of plunging goiters through a retrospective and descriptive study conducted from January 2010 to December 2015. Results: During the five years period, 15 cases of plunging goiter were registered representing 6.35% of thyroidectomy. Among the patients, there were 4 men (26.66%) and 11 women (73.34%). The mean age was 37.84 years. The character “plunging goiter” was noticed on clinical examination and confirmed by imaging. Two cases of hyperthyroidism were recorded. Eso-trachea compression that is characterized by dysphagia and dyspnea was recorded in 7 cases (46.66%), dysphonia in 2 cases (13.33%). The scanner performed in 8 cases showed a goiter with anterior superior mediastinal shift in 84.61%, driving the eso-tracheal axis in 62.5% of cases. The goiters plunged right in 5 cases (33.33%), left in 2 cases (13.33%) and were bilateral in 1 case. Complete thyroidectomy was performed on all patients by exclusive cervical way with as immediate complications, one intraoperative hemorrhage case (n = 1) and one transient hypoparathyroidism case (n = 1). Histological examination of surgical specimens shows no evidence of malignancy. Conclusion: The plunging goiters are rare and their treatment was complete thyroidectomy by exclusive cervical way. Postoperative evolution was uneventful.